Feasibility study of a randomised controlled trial to investigate the effectiveness of using a humanoid robot to improve the social skills of children with autism spectrum disorder (Kaspar RCT): a study protocol. Issue 6 (22nd June 2017) - Mengoni, Silvana E; Irvine, Karen; Thakur, Deepshikha; Barton, Garry; Dautenhahn, Kerstin; Guldberg, Karen; Robins, Ben; Wellsted, David; Sharma, Shivani
Abstract : Introduction: Interventions using robot-assisted therapy may be beneficial for the social skills development of children with autism spectrum disorder (ASD); however, randomised controlled trials (RCTs) are lacking. The present research aims to assess the feasibility of conducting an RCT evaluating the effectiveness of a social skills intervention using Kinesics and Synchronisation in Personal Assistant Robotics (Kaspar) with children with ASD. Methods and analysis: Forty children will be recruited. Inclusion criteria are the following: aged 5–10 years, confirmed ASD diagnosis, IQ over 70, English-language comprehension, a carer who can complete questionnaires in English and no current participation in a private social communication intervention. Children will be randomised to receive an intervention with a therapist and Kaspar, or with the therapist only. They will receive two familiarisation sessions and six treatment sessions for 8 weeks. They will be assessed at baseline, and at 10 and 22 weeks after baseline. The primary outcome of this study is to evaluate whether the predetermined feasibility criteria for a full-scale trial are met. The potential primary outcome measures for a full-scale trial are the Social Communication Questionnaire and the Social Skills Improvement System. We will conduct a preliminary economic analysis. After the study has ended, a sample of 20 participants and their families will be invited to participate in semistructured interviews to explore the feasibility and acceptability of the study's methods and intervention. Ethics and dissemination: Parents/carers will provide informed consent, and children will give assent, where appropriate. Care will be taken to avoid pressure or coercion to participate. Aftercare is available from the recruiting NHS Trust, and a phased withdrawal protocol will be followed if children become excessively attached to the robot. The results of the study will be disseminated to academic audiences and non-academic stakeholders, for example, families of children with ASD, support groups, clinicians and charities. Trial registration number: ISRCTN registry (ISRCTN14156001 ); Pre-results.